Arduino based infrared intrusion detection and motion sensor device with android app - Richards, Sidney Nyasha (Midlands State University, 2020)
Intrusion detection is a series of processes which involves the detection, warning and notification of the arrival of an unwanted entity within the vicinity of installed sensors and the execution of necessary actions required to be performed so as to alert the members of the asset to be monitored and increase the security of the building simultaneously. The growth of intrusion detection systems is largely attributable to a decrease in costs plus enhancements to the technology in terms of additional miniaturization and software optimization that, together, have made this type of security more accessible. In line with this notion this study was carried out to develop a working prototype that uses the ultrasonic sensor for intrusion detection which is then linked with other components to come up with a robust prototype. The current technological developments, notably the improvements in precision and reduced costs of developing and running intrusion detection systems, have served very much as key drivers for the implementation of such systems in many industries. The ideas implemented were inferred from previous models which used intrusion detection devices as a tool for constant monitoring of assets. This document highlights all the necessary steps undergone in the development of the prototype from the planning phase to the operation phase. The intrusion detection prototype which is composed mainly of an ultrasonic sensor, 4x4 keypad membrane and an LCD is interfaced with an android application to enable remote control of such systems which was not there before. The future scope of this study is mainly centred on having the system protect itself from the intruder. By using intrusion detection devices, institutions believe they will be able to provide the level of security necessary to reduce the risk of theft, while also reducing operational risks through more efficient constant monitoring devices.